Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s13104-018-3215-y
|View full text |Cite
|
Sign up to set email alerts
|

Patient delay in seeking tuberculosis diagnosis and associated factors in Hadiya Zone, Southern Ethiopia

Abstract: ObjectiveTo assess patient delay in seeking tuberculosis diagnosis and associated factors in Hadiya Zone, Southern Ethiopia.ResultsThe median patient delay in tuberculosis diagnosis in Hadiya Zone was found to be 30 days. Socioeconomic and perception related factors were identified as independent predictors for tuberculosis diagnosis delay. Socioeconomic characteristics like urban residence [OR 2.36; CI 1.64–3.40], religious views [OR 1.24; CI 1.73–7.0], low monthly income [OR 3.38; CI 2.01–5.66] were statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 18 publications
5
33
2
Order By: Relevance
“…Compared to delay studies conducted in Ethiopia, we report shorter patient delay of 31 days from northern Ethiopia [41], 30 days reported from Hadiya zone in southern Ethiopia [36], 60 days in Addis Ababa [35] and more than 2 months pretreatment duration from Sidama in southern Ethiopia [42], but longer than study from southern Ethiopia that reported 4 days [43]. There is much reduction in the overall delay as a result of increased coverage of health service, better awareness, difference in the study period and changes in socioeconomic conditions.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Compared to delay studies conducted in Ethiopia, we report shorter patient delay of 31 days from northern Ethiopia [41], 30 days reported from Hadiya zone in southern Ethiopia [36], 60 days in Addis Ababa [35] and more than 2 months pretreatment duration from Sidama in southern Ethiopia [42], but longer than study from southern Ethiopia that reported 4 days [43]. There is much reduction in the overall delay as a result of increased coverage of health service, better awareness, difference in the study period and changes in socioeconomic conditions.…”
Section: Discussioncontrasting
confidence: 70%
“…Studies from Ethiopia reported delays to be associated with educational status, poverty, awareness about TB and accessibility of TB services [35,36] with higher proportion of health system delay from northern Ethiopia [37]. However, most studies were limited to specific population groups and quantitative designs.…”
Section: Introductionmentioning
confidence: 99%
“… 30 At the individual level factors influencing total delay includes socioeconomic status, educational level, and cultural background. 31 In our study, the peak of female cases appeared later than that of male cases, which may be explained by the significantly longer total delay of female cases than male cases in developing countries. 32 The availability of health services also has an impact on diagnosis delay.…”
Section: Discussionmentioning
confidence: 45%
“…To compare with similar studies in SEA countries, proportions of delayed careseeking among patients were 34.1% in Myanmar migrant populations in Thailand, 67.4% in Nepal, 29% in South India and 75.3% in East Malaysia. These percentages of patient care-seeking delay differed because they depended on socio-economic status, awareness of the patients, receiving information on TB for prevention and treatment and availability of health care facilities [26][27][28][29]. The national TB control program should consider introducing aggressive active casefinding mechanisms among targeted high risk populations.…”
Section: Discussionmentioning
confidence: 99%